Método de Monte Carlo para o estudo de sistemas magnéticos bidimensionais - Silva, George Frederick Tavares da (2008)
Employing the Monte Carlo Method, studied is two-dimensional magnetic systems. The phase transition that occurs in Ising model was also investigated for the two-dimensional XY model, or also called 2D XY in the literature. There is this model an unusual transition type Kosterlitz-Thouless-Berezinskii, involving vortices of spins which unbinding in a temperature T_{KT}. However, you can see the transition without the presence of vortices for small systems as was done in this work. The implementation of the method cited in the two models will be detailed and then used in the study of magnetic bylayers systems characterized by the existence of planning ferromagnetic (FM) and antiferromagnetic (AFM). They will be then reproduced through simulations, curves of magnetization in relation to the magnetic field, with the goal of find the conditions in which the phenomenon known as Exchange Bias occurs. This is because the existence of an interface FM-AFM, which will be the focus of research.